Hallazgo de Matelea balansae (Apocynaceae) después de 143 años de su único registro - Keller, Hector Alejandro (2018)
An occurrence of Matelea balansae (Apocynaceae), a species that was previously known only from a single find from Paraguay in 1874, is first reported from Misiones, Argentina. Adult plants, buds and flowers are displayed.